The modifying role of emotion regulation in predicting sleep quality based on coronary anxiety and stress caused by the Covid-19 virus: Society public health - Hatamian, Peyman; Rasoulzadeh Tabatabai, Seyed Kazem; Rahdar, Mohammad (Researcher Bulletin of Medical Sciences, 2023)
Background and Objective: Since the Covid-19 virus has caused many psychological problems for humans since its initial outbreak, Therefore, the present study aimed to determine the moderating role of emotion regulation in predicting sleep quality based on coronary anxiety and stress caused by the Covid-19 virus. Materials and Methods: The present study was a descriptive correlational study. The statistical population of the study includes all the people of Iran in 2020, which were selected through questionnaires that were placed electronically on popular sites, channels and media, and finally, 239 people answered the questionnaires. Research tools include; Alipour Corona Anxiety Questionnaire (2020), Lavibund and Lavibund Stress Questionnaire (1995) (which was presented to the participant with emphasis on Covid-19 syndrome), Emotional Regulation Questionnaire (ERQ-10) and Pittsburgh Sleep Quality Questionnaire (1989). The obtained data were studied by descriptive statistics, correlation coefficient, regression analysis and analyzed simultaneously and hierarchically by SPSS-23 statistical software. Results: The results showed that anxiety and stress caused by Covid-19 have a significant relationship with sleep quality (P <0.001), so that both can cause 0.41 changes in sleep quality. Also, the results of hierarchical regression analysis to predict the quality of sleep from the multiple of the deviating scores of anxiety and stress confirmed the moderating role of emotion regulation, which was significant at the level (P <0.001). Conclusions: Therefore, it can be concluded that anxiety and stress caused by Covid-19 can predict the quality of sleep and in the meantime, emotion regulation can play a moderating role, therefore it is suggested Health professionals focus on the important role of emotion regulation in critical situations.